PENGARUH KEBERSIHAN,LINGKUNGAN KERJA TERHADAP KEJADIAN TB PADA PETUGAS KESEHATAN - Cory Febrina; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt; Genius Umar; Yulkifli Yulkifli; Nurhasan Syah; Imelda Rahmayunia Kartika; Fitrianola Rezkik; Rina Mariyana; Mesi Yunia Sari; Meladina Meladina; Cici Aprilliani; Kiki Amelia; Fanny Yuliana Batubara; Rindi Genesa Hatika; Washilla Audia; Abdi Iswahyudi Yasril; Juli Hendrita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Many cases of disease in healthcare workers are suspected to be related to environmental conditions, but the relationship between these two factors has not been clearly described. This study conducted a literature review regarding the influence of environmental conditions on occupational diseases in healthcare workers. Relevant articles were searched through electronic databases such as PubMed, ProQuest, Google Scholar, and Springer, with publications spanning the last 5 years. The search used the English-language keywords: